Inisiasi Panduan Sasaran Keselamatan Pasien Unit Rawat Jalan di Rumah Sakit - Ulfah, Maria; Handiyani, Hanny; Kuntarti, Kuntarti (FORIKES, 2025)
Improving the quality and safety of patients in outpatient units of hospitals is a crucial aspect in ensuring the quality of health services. However, the implementation of patient safety targets in outpatient units still faces challenges. Good management planning is very important as a basis for patient safety targets in outpatient units of hospitals. This study aimed to identify the needs and problems in implementing patient safety targets in outpatient units of hospitals. This study was a case study research with the Kotter's Eight-Step Plan theory of change approach. Data collection was carried out in the period from April 23 to May 2, 2024 through interviews, questionnaires and observations. The research informants were 25 outpatient unit nursing staff. The results of the study showed that the planning function of the head of the room related to patient safety targets was not optimal, so the preparation of patient safety guidelines was prioritized as a solution. The implementation of the guideline was carried out using the Kotter's Eight-Step Plan theory approach, especially in stages 1-4, including problem identification, team formation, vision development, and socialization. Furthermore, it was recommended to improve the implementation of patient safety targets including the ratification of the guideline, training for nursing staff, and periodic evaluation. It was further concluded that this study emphasizes the importance of a structured change approach to improve the quality of nursing care and patient safety.Keywords: patient safety; outpatient unit; service quality; Kotter's theory of change ABSTRAK Peningkatan mutu dan keselamatan pasien di unit rawat jalan rumah sakit menjadi aspek krusial dalam menjamin kualitas pelayanan kesehatan. Namun, penerapan sasaran keselamatan pasien di unit rawat jalan masih menghadapi tantangan. Perencanaan manajemen yang baik sangat penting sebagai dasar sasaran keselamatan pasien di unit rawat jalan rumah sakit. Studi ini bertujuan untuk mengidentifikasi kebutuhan dan permasalahan dalam penerapan sasaran keselamatan pasien di unit rawat jalan rumah sakit. Studi ini merupakan penelitian studi kasus dengan pendekatan teori perubahan Kotter’s Eight-Step Plan. Pengumpulan data dilakukan pada periode 23 April hingga 2 Mei 2024 melalui wawancara, kuesioner dan observasi. Informan penelitian adalah 25 staf keperawatan unit rawat jalan. Hasil penelitian menunjukkan bahwa fungsi perencanaan kepala ruangan terkait sasaran keselamatan pasien belum optimal, sehingga diprioritaskan penyusunan panduan keselamatan pasien sebagai solusi. Implementasi panduan dilakukan dengan pendekatan teori Kotter’s Eight-Step Plan khususnya pada tahapan 1-4, meliputi identifikasi masalah, pembentukan tim, penyusunan visi, dan sosialisasi. Selanjutnya direkomendasikan untuk meningkatkan penerapan sasaran keselamatan pasien meliputi pengesahan panduan, pelatihan bagi staf keperawatan, dan evaluasi berkala. Selanjutnya disimpulkan bahwa penelitian ini menekankan pentingnya pendekatan perubahan terstruktur untuk meningkatkan mutu pelayanan keperawatan dan keselamatan pasien.Kata kunci: keselamatan pasien; unit rawat jalan; mutu pelayanan; teori perubahan Kotter